2006
DOI: 10.1158/0008-5472.can-05-4519
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Retinoic Acid–Binding Protein II Is a Direct Transcriptional Target of MycN in Neuroblastoma

Abstract: Neuroblastoma is a heterogeneous disease in which 22% of tumors show MycN oncogene amplification and are associated with poor clinical outcome. MycN is a transcription factor that regulates the expression of a number of proteins that affect the clinical behavior of neuroblastoma. We report here that cellular retinoic acid-binding protein II (CRABP-II) is a novel MycN target, expressed at significantly higher levels in primary neuroblastoma tumors with mycN oncogene amplification as compared with non-MycN-ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 43 publications
5
19
0
2
Order By: Relevance
“…We found that MycN induction rapidly upregulated livin expression. This system has been widely used to investigate MycN regulation of a number of target genes in neuroblas- toma (25,27,28). Our results with the MYCN-inducible system complement and reinforce our data from the MYCNknockdown experiments.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that MycN induction rapidly upregulated livin expression. This system has been widely used to investigate MycN regulation of a number of target genes in neuroblas- toma (25,27,28). Our results with the MYCN-inducible system complement and reinforce our data from the MYCNknockdown experiments.…”
Section: Discussionsupporting
confidence: 85%
“…We detected a consensus MycN binding domain within the 5' proximal sequence of the putative livin promoter. Similar direct binding of MycN to E-boxes within the target promoters of MDM2, MRP1 and CRABII in neuroblastoma cells have been reported as evidence that MycN positively regulates expression of these genes (25,27,28). We are currently characterizing the role of this MycN binding site in the livin promoter by mutation/deletion experiments.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, several known MYCN-regulated genes (NME2 [20], CRABP2 [21], LIF [22], MDM2 [23], MIR17HG [24], PRMT1 [25], MCM7 [26], MCM8 [26], ODC1 [27], BIRC5 [28], LUC7L [29], TWIST1 [30], RAB5C [31], AURKA [31], H1F0 [31], and MYBL2 [32]) were successfully detected in the ChIP-seq experiments (Supplementary Figure S2). To study the distribution of MYCN binding around promoter sequences, we aligned the peaks with the annotated transcriptional start sites (TSSs), which were provided by RefSeq.…”
Section: Resultsmentioning
confidence: 99%
“…Соответ-ственно, возникает петля положительной обратной связи, приводящая к усилению малигнизации клеток. Авторы даже предлагают использовать CRABP2 в ка-честве мишени для таргетной терапии при данном заболевании [99].…”
Section: функции Crabp2unclassified